Thrown in at the deep end: a qualitative study with physicians on the purpose and challenges of discharge interviews - Morschek, Lorena; Schultz, Jobst-Hendrik; Wigbels, Ricarda; Gebhardt, Nadja; Derreza-Greeven, Cassandra; Friederich, Hans-Christoph; Noll, Alexandra; Unger, Inga; Nikendei, Christoph; Bugaj, Till Johannes (Postgraduate medicine, 2024)
Against the backdrop of poor discharge communication in hospitals, this study explores the purpose of discharge interviews from the physicians’ perspective and the challenges they are confronted wi...
Online veröffentlicht: 20 Februar 2024
Gesehen am 29.05.2024